Covalent organic frameworks (COFs): from design to applications - Ding, San-Yuan; Wang, Wei (Chemical Society reviews, 2013)
Covalent organic frameworks (COFs) represent an exciting new type of porous organic materials, which are ingeniously constructed with organic building units via strong covalent bonds. The well-defined crystalline porous structures together with tailored functionalities have offered the COF materials superior potential in diverse applications, such as gas storage, adsorption, optoelectricity, and catalysis. Since the seminal work of Yaghi and co-workers in 2005, the rapid development in this research area has attracted intensive interest from researchers with diverse expertise. This critical review describes the state-of-the-art development in the design, synthesis, characterisation, and application of the crystalline porous COF materials. Our own opinions on further development of the COF materials are also presented for discussion (155 references). This critical review describes the state-of-the-art development in the design, synthesis, characterisation, and application of the crystalline porous COF materials.